Isolation and Identification of Brucella Melitensis in Diseased Nile Tilapia, Oreochromis Niloticus from a Commercial Fish Farm in Tamil Nadu, India - A. Uma; G. Rebecca; S. Gangatharan; N. Palanivel (The Indian Veterinary Journal, 2024)
Brucellosis is a zoonotic bacterial disease affecting livestock with fewer reports in fishes. The present study reports the isolation and identification of Brucella melitensis from diseased Nile Tilapia, Oreochromis niloticus from a commercial fish farm. The diseased fish with clinical sings were collected and the organs viz., liver, kidney, spleen and intestine were aspectically dissected for isolation of  bacterial pathogens. The bacteria isolate (H1/SRLAAH/2019) from the liver of the infected fish was characterised by the biochemical tests as Brucella sp. and confirmed by 16S rRNA gene sequencing analysis as B.melitensis. This is the first report on the isolation and identification of B. melitensis from O. niloticus in India.